Glucagon-Like Peptide-1: A Focus on Neurodegenerative Diseases - Grieco, Maddalena; Giorgi, Alessandra; Gentile, Maria Cristina; d’Erme, Maria; Morano, Susanna; Maras, Bruno; Filardi, Tiziana (Frontiers in Neuroscience, 2019)
Diabetes mellitus is one of the major risk factor for cognitive dysfunction. The pathogenesis of hyperglycemia involved in brain impairment is complex and includes mitochondrial dysfunction, neuroinflammation, neurotransmitters’ alteration and vascular disease, which implicate cognitive impairment, neurodegeneration, loss of synaptic plasticity, brain aging and dementia. Several studies have shown the influence of glucagon-like peptide-1 (GLP-1) on neuronal functions such as thermogenesis, blood pressure control, neurogenesis, neurodegeneration, retinal repair, and energy homeostasis. Moreover, the modulation of GLP-1 activity can influence amyloid β peptide aggregation in Alzheimer’s disease (AD) and dopamine levels in Parkinson’s disease (PD). Glucagon-like peptide-1 Receptor Agonists (GLP-1RAs) have shown beneficial actions in animal models of brain ischemia, such as the reduction in cerebral infarct area and the improvement in neurological deficit, mainly through the inhibition of oxidative stress, inflammation and apoptosis. They might exert other favourable effects, such as the reduction of cognitive impairment induced by diabetes or obesity. In animal models of diabetes and neurodegeneration associated with cognitive decline, they have shown to improve learning and memory by modulating synaptic plasticity. Moreover, they reduced hippocampal neurodegeneration, by increasing the number of progenitor cells. Besides this, there is growing evidence about neuroprotective effects of GLP-1RAs in animal models of neurodegenerative diseases, regardless of diabetes. In animal models of PD they mainly protected motor activity and dopaminergic neurons. They seem to improve nearly all neuropathological features and cognitive functions in animal models of AD. Although further studies in humans are needed, GLP-1RAs are a promising therapy for diabetes-associated cognitive decline, PD and AD.